Stepwise Weakening of the Pliocene Leeuwin Current - David De Vleeschouwer; Benjamin F. Petrick; Alfredo Martínez‐García (Geophysical Research Letters)
Abstract The Indonesian Throughflow (ITF) operates as an important link in global thermohaline circulation, and ITF variability probably modulated Pliocene climate change. Yet, whether ITF variability accounted for oceanographic change south of Northwest Cape remains controversial. Here, we present a multiproxy oceanographic reconstruction from the Perth Basin and reconstruct the Pliocene history of the Leeuwin Current (LC). We show that the LC was active throughout the Pliocene, albeit with fluctuations in intensity and scope. Three main factors controlled LC strength. First, a tectonic ITF reorganization caused an abrupt and permanent LC reduction at 3.7 Ma. On shorter timescales, eustatic sea level and direct orbital forcing of wind patterns hampered or promoted the LC. At 3.3 Ma, for instance, LC intensity plunged in response to a eustatic ITF restriction. Site U1459 then fell outside the extent of a weakened LC, and the latitudinal sea surface temperature gradient along West Australia doubled its steepness.